Damen (Rice Straw) Waste and Eggshell as Liquid Organic Fertilizer: An Effort for New Business Opportunities - Luluk Muthoharoh; Reni Permata Sari; Muhammad Putra Pamungkas; Agus Komarudin (Smart Society, 2022)
The dissemination activity of exploring damen (rice straw) waste as liquid organic fertilizer is a form of Tridharma of higher education for community service practiced by four lecturers. This activity has several main goals: increasing public awareness, particularly among residents of RT 20 Sadar Sriwijaya Village, Bandar Sribhawono District, about the importance of utilizing damen waste to be used as liquid organic fertilizer, rather than being thrown away or simply burned after the harvesting process is complete. Socialization activities are carried out in two ways: material delivery and practice daily. Based on the socialization, it was discovered that the participants achieved the socialization's objectives with good criteria in general. As a result, the public knowledge, particularly among residents of RT 20 Sadar Sriwijaya Village, Bandar Sribhawono District, East Lampung Regency, on the use of damen waste and chicken eggshell waste is still low, so socialization is required to raise awareness of the use of agricultural waste as fertilizer